The Ethics of Surveillance in Times of Emergency - Macnish, Kevin; Henschke, Adam (Oxford University Press, 2023)
The Covid-19 pandemic is arguably the first international emergency of the twenty-first century. In order to respond to this emergency, countries and governments around the world were forced to engage in a range of actions and policies that would not otherwise have been permitted. Looking in particular at the use of surveillance technologies, this book examines the challenge of ethics in emergencies. What can states do to keep their populations safe, what can citizens expect of their governments, and when are those government actions unjustified? By looking at the use of surveillance in times of emergency, this book explores ethical, philosophical, political, and social concepts, challenges them, and offers a set of views on where those concepts may evolve into the future. As a global population, we will be faced with emergencies, and it is possible that these will also be global in their impact. The ethics of surveillance in times of emergency is both of its time, and ongoing; we must learn our lessons from the last emergency, to be prepared for the next ones.